Quality Of Dutch Eggplant Fruit Dodol With Added Sugar - Putri Yanti, Aimi Dwi; Holinesi, Rahmi; Gusnita, Wiwik; Siregar, Juliana (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Fruit dodol is a type of  processed agricultural product that is semi-wt, white to brown in color, made from a mixture of sticky rice flour, sugar and coconut milk. This ressearch aims to analyze the quality of Dutch eggplant dodol bg adding variations of sugar of 0 gr, 100 gr, 150 gr and 200 gr. Regarding the quality of shape, color, aroma, texture and taste of dodol This type of research is a pure experiment with a completely randomized design (RAL) method consisting of 4 treatment and 3 repetitions, to analyze the quality of tamarillo fruit dodol with variations in the addition of sugar. organoleptic involving 15 students of Culinary Management, Family Welfare Science. The data obtained was then tabulated and continued with ANOVA, if F count > F table then continued with the Duncan test. The results of the research showed that the use of variations in sugar content on the quality of Dutch eggplant dodol had a significant effect on the quality of color and taste. Meanwhile, the shape, aroma and texture indicators did not have a significant effect. The highest overall achievement scores were neat shape 3.33 (200 gr), heart red color 3.83 (200 gr), tamarillo fruit aroma 2.91 (200 gr), chewy texture 3.33 (200 gr), and sweet taste 3.24 (200 gr), tamarillo fruit taste 3.58 (200 gr). The results of the quality of Dutch eggplant dodol with variations in the addition of the best sugar content were in the fourth treatment (X3) with variations in the addition of 200 gr of sugar).